1993
DOI: 10.1364/ol.18.000941
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced second-harmonic generation in azo-dye polymers

Abstract: The permanent all-optical poling of an azo-aromatic acrylic copolymer is experimentally demonstrated by seeding preparation in a backward phase-conjugation geometry. The microscopic mechanism involves an orientational hole burning followed by orientational redistribution caused by trans-to-cis isomerization of the azo-dye chromophores. The characteristic kinetics of monitored by second-harmonic generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(92 citation statements)
references
References 11 publications
0
92
0
Order By: Relevance
“…First, it leads to the generation of second harmonic radiation from a medium which is macroscopically isotropic. [10][11][12][13][14][15][16][17] Second, it has been demonstrated that by employing this experiment in a time resolved geometry it is possible to extract quite new information on the orientational dynamics of solutions. 10 The purpose of this paper is to treat the theory underlying a nondegenerate sixwave mixing processes in a rigorous and fully quantized manner, to compare the results with experimental measurements, and to act as a precursor to a forthcoming one on dynamical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…First, it leads to the generation of second harmonic radiation from a medium which is macroscopically isotropic. [10][11][12][13][14][15][16][17] Second, it has been demonstrated that by employing this experiment in a time resolved geometry it is possible to extract quite new information on the orientational dynamics of solutions. 10 The purpose of this paper is to treat the theory underlying a nondegenerate sixwave mixing processes in a rigorous and fully quantized manner, to compare the results with experimental measurements, and to act as a precursor to a forthcoming one on dynamical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] Relations closely related to (5) have also been derived by several other groups considering the effect of simultaneous irradiation at ω and 2ω. Most often the experimentally straightforward case of co-propagation of ω and 2ω has been considered.…”
Section: Measurementmentioning
confidence: 89%
“…8,9,[13][14][15] This was first demonstrated by Nunzi and co-workers, who have gone on to exploit the technique as a means of "optical poling" of polymers. [16][17][18] Our objective in this paper is to demonstrate that observations of the induced second harmonic intensity as a function of delay time records the decay, through orientational diffusion, of the induced polar order in solution. In particular we will provide experimental verification that this time delayed signal yields odd moments (l ) 1 and l ) 3) of the orientational distribution function.…”
Section: Introductionmentioning
confidence: 98%
“…A significant number of polymers functionalized, in particular, with DR1 dye in the side chain are reported (Blanchard et al 1993a(Blanchard et al , 1993b as cited in Natansohn & Rochon, 2002;Loucif-Saibi et al, 1993 as cited in Natansohn & Rochon, 2002;Hill et al, 1995as cited in Natansohn & Rochon, 2002 to have been submitted to photoassisted alignment, thus achieving improved NLO properties. An all-optical poling, in which the aligning electric field is actually generated by the laser light has also been envisaged since 1993 on DR1M-MMA copolymer (Charra et al, 1993;Chalupczak et al, 1996) and subsequently applied to a new phosphine oxide azo-dye-MMA copolymer (Fiorini et al, 1997) achieving increased transparency with respect to the DR1 functionalized material, together with large secondorder properties. Differently from the polymeric DR1M-MMA material, efficient optical poling of thin films of norbornene functionalized with azo-dye have also been achieved, but without appreciable enhancement of second-order susceptibility, however, in the related polymeric poly-norbornene derivative, due probably to the increased rigidity of the polynorbornene backbone with respect to the poly-MMA backbone (Churikov et al, 2000).…”
Section: Fig 3 Statistical Photoorientation Of Azomoleculesmentioning
confidence: 99%